Wavelet-fuzzy speed indirect field oriented controller for three-phase AC motor drive – Investigation and implementation - Padmanaban, Sanjeevikumar; Daya, Febin J.L.; Blaabjerg, Frede; Wheeler, Patrick; Szcześniak, Pawel; Oleschuk, Valentin; H.Ertas, Ahmet (Elsevier, 2016)
Three-phase voltage source inverter driven induction motor is used in many medium- and high-power applications. Precision in speed of the motor play vital role, i.e. popular methods of direct/indirect field-oriented control (FOC) are applied. FOC is employed with proportional–integral (P-I) or proportional–integral–derivative (P-I-D) controllers and they are not adaptive, since gains are fixed at all operating conditions. Therefore, it needs a robust speed controlling in precision for induction motor drive application. This research paper articulates a novel speed control for FOC induction motor drive based on wavelet-fuzzy logic interface system. In specific, the P-I-D controller of IFOC which is actually replaced by the wavelet-fuzzy controller. The speed feedback (error) signal is composed of multiple low and high frequency components. Further, these components are decomposed by the discrete wavelet transform and the fuzzy logic controller to generate the scaled gains for the indirect FOC induction motor. Complete model of the proposed ac motor drive is developed with numerical simulation Matlab/Simulink software and tested under different working conditions. For experimental verification, a hardware prototype was implemented and the control algorithm is framed using TMS320F2812 digital signal processor (dsp). Both simulation and hardware results presented in this paper are shown in close agreement and conformity about the suitability for industrial applications.